Diffusion tensor brain imaging in forensic radiology. Issue 4 (December 2015) - Berkovitz, Nadav; Abrahamy, Michael; Gottlieb, Paul; Vasserman, Margarita; Tal, Sigal
Abstract: Objectives: Evaluation of changes in DTI parameters in post-mortem (PM) cadaveric vs. antemortem (AM) healthy control brains based on eigenvalues at <24 h PMI. Methods and materials: The in-situ DTI brain scans of 10 PM subjects were compared to 10 AM controls. DTI metrics were measured from 25 ROIs for each brain in the gray and white matter. Results: PM eigenvalues ( λ 1, λ 2, λ 3) were significantly lower than in the AM controls, independent of tissue type. Longitudinal diffusivity was more affected than transverse (control vs. PM, for λ 1, λ 2 and λ 3 in mm 2 /s×10 −3 : 0.96, 0.74, 0.58 vs. 0.27, 0.20, 0.15 for gray matter and 1.52, 0.44, 0.25 vs . 0.33, 0.10, 0.05 for white matter, p <0.0001). FA was significantly higher PM for gray matter (0.28 PM vs. 0.22 control, p =0.003) but similar for white matter (0.73 PM vs. 0.75 control, p =0.4). ADC values were lower for PM (0.73 control vs. 0.16 PM and 0.76 control vs. 0.21 PM, in white/gray matter respectively, p <0.0001; all units mm 2 /s×10 −3 ). Conclusion: Both longitudinal diffusivity, transverse diffusivity and ADC are reduced PM. The lack of FA changes in white matter PM implies that FA changes in stroke are due to the ischemic cascade rather than direct cell death. Gray matter of the caudate showed an increase in FA similar to what is seen in a number of both degenerative and inflammatory pathologies. Highlights: DTI parameters in 10 post-mortem cadaveric vs. 10 antemortem healthy control brains <24 h PMI. ROIs for each brain in the gray and white matter. Longitudinal diffusivity, transverse diffusivity and ADC are reduced post-mortem. Lack of FA changes in white matter, unlike stroke, possible due to ischemic cascade rather than direct cell death. Gray matter in caudate showed an increase in FA similar to degenerative and inflammatory pathologies.